A framework for analyzing participatory plant breeding approaches and results - Sperling, L.; Ashby, Jacqueline A.; Smith, M.E.; Weltzien, Eva; McGrath, S. (Springer, 2001)
Participatory Plant Breeding (PPB) involves scientists, farmers, and others, such as consumers, extensionists, vendors, industry, and rural cooperatives in plant breeding research. It is termed `participatory' because many actors, and especially the users, can have a research role in all major stages of the breeding and selection process. While some have argued that commercial, private sector plant breeding has long been client-driven, or `participatory' under another name, the application of `PPB' to reach poor client groups, to breed for high-stress, heterogeneous environments and to incorporate diverse traits to meet specific client preferences is resulting in fundamental changes in the way plant genetic resources are being managed. PPB merits analysis as a separate approach. The notion of `PPB' is a relatively recent one: detailed inventories show that most of the 65 `longer-term' cases have begun within the last 10 years, whether they were located in public sector or non-governmental crop improvement programs. With such `newness'comes a wealth of terminology and divergent technical, social and organizational strategies under the general rubric of `PPB'. This article aims to set up a framework for differentiating among PPB approaches. Only by discriminating among cases can one understand how each PPB approach can lead to a different outcome, and so be able to make informed choices about which approach to pursue. The key variables explored for discriminating among PPB approaches include: the institutional context, the bio-social environment, the goals set, and the kind of `participation' achieved, (including the stage and degree of participation and the roles different actors undertake). It is only when these variables are clearly described that current and potential practitioners can start to link the `type of PPB' employed (method and organizational forms) with the type of impacts achieved. An ending illustration of ongoing PPB programs suggests the practical utility of this `PPB framework'.